Encephalitozoon cuniculi infection among immunocompromised and immunocompetent humans in Egypt - Somaia Saif ABU-AKKADA; Eman Dorry Hussein EL KERDANY; Rasha Fadly MADY; Radwa Galal DIAB; Gehan Abd Elatti KHEDR; Karam Imam ASHMAWY; Wael Mohamed LOTFY (Iranian Journal of Parasitology, 2015)
Background: Encephalitozoon cuniculi infects a wide range of homoeothermic animals, including man. Complications due to this microsporidian have been reported only in immunocompromised patients. Reports on E. cuniculi in immunocompetent humans are lacking, most probably, because it is not linked to any clinical manifestations in such hosts. The present work was carried out with the aim of studying, for the first time in Egypt, the prevalence of E. cuniculi infection of urinary tract among non-HIV immunocompromised patients and immunocompetent individuals. It tested also the influence of some factors on the risk of infection.